Individualized Strategies for Intraoperative Localization of Non-palpable Pulmonary Nodules in a Hybrid Operating Room - Leow, Osbert Qi Yao; Chao, Yin-Kai (Frontiers in Surgery, 2019)
Background: Precise preoperative localization of small pulmonary nodules is a key prerequisite to their successful excision. With the advent of hybrid operating rooms (HORs), a patient-tailored approach encompassing simultaneous localization and removal of small pulmonary nodules has become feasible. In this study, we describe our individualized image-guided video assisted thoracoscopic surgery (iVATS) strategies implemented within a HOR environment. Specifically, localization was performed through different marking approaches (single- vs. double-marker) and access routes [percutaneous technique with Dyna-computed tomography (DynaCT) imaging vs. electromagnetic navigation bronchoscopy (ENB)]. Methods: Between April 2017 and November 2018, a total of 159 consecutive patients (harboring 174 pulmonary nodules) were treated with iVATS. The marking approach and access route were individually tailored according to lesion localization and its distance from the pleural surface. The efficacy and safety of our iVATS technique were determined through a retrospective review of clinical charts. Results: All of the localization procedures were performed in a HOR by a single team of thoracic surgeons. The mean tumor size on preoperative CT was 8.28 mm (95% confidence interval [CI]: 7.6–8.96 mm), whereas their mean distance from the pleural surface was 9.44 mm (95% CI: 8.11–10.77 mm). Of the 174 tumors, 150 were localized through a percutaneous DynaCT-guided approach (single-marker: 139, dual-marker: 11), whereas localization in the remaining 24 was accomplished via the ENB-guided approach (single-marker: 4; dual-marker: 20). The mean localization time was 17.78 min (95% CI:16.17–19.39 min). The overall localization success rate was 95.9%. We failed to localize a total of seven nodules either because of technical complications (pneumothorax, n = 3; microcoil dislodgement; n = 1) or machine failure (n = 3). No operative deaths were observed, and the mean length of postoperative stay was 3.65 days (95% CI: 3.19–4.11 days). Conclusions: The use of tailored marking approaches and access routes allowed us to individualize the iVATS procedure for small pulmonary nodules, ultimately promoting a more patient-centered workflow.